Effects of Methanol Extract of Piper chaba Stem Bark on Acute Inflammation in rats (Faridpur Medical College Journal, 2012)
The plant Piper chaba Hunter (Piperaceae), a climbing glabrous shrub grows in plenty in southern Bangladesh. Popularly known as 'Choi' it is used as spices and believed to have medicinal value in a wide variety of disease conditions including arthritis, asthma, bronchitis and piles. In the present study, effect of methanol extract of Piper chaba stem bark on acute inflammation has been reported. The anti-inflammatory effect was studied in rats by injecting 0.1ml of 1% carrageenan suspension into the planter surface, where oedema of the rat's hind paw was used as an index of acute inflammation. Methanol extract of Piper chaba stem bark given orally 1 hour before injection at doses of 125 and 250 mg/kg body weight, produced significant (p< 0.05) anti inflammatory effect compared to control and the percentage of inhibition of oedema formation was 33% and 35% respectively, which however was less compared to aspirin (46%) and hydrocortisone (56%). The result suggest that in case of acute inflammation, Piper chaba stem bark possess mild to moderate anti inflammatory effect compared to that of aspirin and hydrocortisone.DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10294Faridpur Med. Coll. J. 2012;7(1): 26-28